Respuesta agronómica del cultivo zucchini (Cucurbita pepo L.), con la aplicación de abonos orgánicos en la parroquia Nueva Unión del cantón Valencia provincia de Los Ríos. - Alcivar Cevallos, Kerly Jazmin (2023)
The main objective of the research project was to evaluate the agronomic response of zucchini (Cucurbita pepo L.), with the application of two types of organic fertilizers (Humus and Biol), with a categorical treatment called control. ), with the application of two types of organic fertilizers (Humus and Biol), with a categorical treatment called control, using a completely randomized block design with 7 replications, 2 treatments and a control, with a total of 21 plots, taking into account that each plot has a number of 5 plants each, in which the 21 plots were divided by lot into 3 equal parts, giving us a total of 105 plants, carrying out an economic valuation of the treatments in their totality used in the variables to analyze, investigate and interpret and determine their economic value during the 16 weeks, obtaining data based on plant height (cm), stem diameter (cm), leaf circumference (cm), number of leaves, days of flowering, number of flowers per plant, number of fruits per plant and fruit weight in grams, where the best results were obtained by the crop that was applied the organic fertilizer represented by code T1 (Humus) at all times from transplanting the crop until harvest, the benefit/cost ratio reached with better results through the application mentioned above, with a value of 1.17 USD in favor (for each dollar reached 1.17 USD).